SITUASI TERKINI VEKTOR DENGUE [Aedes aegypti Lin] DI JAWA TENGAH, INDONESIA - Sayono -; Ulfa Nurullita (Universitas Muhammadiyah Semarang, 2015)
Dengue viruses infection spread widely around the world causing 3,97 milliard people at risk, including Indonesian. Anti-dengue virus medicine and vaccine have not been available so that the prevention efforts were focused on controlling of Aedes population. This research was focused on recent situation of Aedes aegypti mosquitoes: population density, productive habitat and insecticide susceptibility. Dengue vector survey involved 20 houses around the Dengue patient’s house in six districts in Central Java Province, and the domestic water containers as object. The measured variables are type, material, color, place, and water pH of containers, and mosquito larvae existence. Larvae were reared to become mosquito stadia, and subjected to species identification morphologically and WHO-standard susceptibility test with Permethrin-0,75%, Deltamethrin-0,05% and Malathion-5% insecticide compounds. Result shows that the Aedes aegypti population indices (House index, Container index and Breteau index) ranged 27.3-55.2, 19.1-53.8, and 44.8-72.7 percents. Mosquito larvae were found in seven types of container, respectively. Wall color and water pH of containers were significantly correlated to Aedes aegypti larvae existence (p<0.05). Mortality rate of mosquitoes in bioassay test were 17%, 67% and 100% based on permethrin-0.75%, Deltamethrin-0.05% and Malathion-5% compounds.Keywords: Aedes aegypti, Dengue endemic area, Central Java